2019
DOI: 10.1177/0022487119879895
|View full text |Cite
|
Sign up to set email alerts
|

Education Policy and Black Teachers: Perspectives on Race, Policy, and Teacher Diversity

Abstract: This article examines interview responses from prominent education researchers who were asked to consider the role of major educational policies in the underrepresentation of Black teachers in public schools. Participants considered policies related to accountability and market reforms including testing, school choice and charter schools, and alternative teacher education. Although participants agreed that Black teachers contribute greatly to academic achievement for students, their views differed about whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In addition, educational leaders should also be represented along lines of differences. Currently, BIPOC educators are underrepresented in teaching and administration (White et al, 2020).…”
Section: Discussion Recommendations and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, educational leaders should also be represented along lines of differences. Currently, BIPOC educators are underrepresented in teaching and administration (White et al, 2020).…”
Section: Discussion Recommendations and Conclusionmentioning
confidence: 99%
“…In addition, educational leaders should be represented along lines of differences. Currently, BIPOC educators are underrepresented in teaching and administration (White et al, 2020). This study provides recommendations to leaders and policymakers to diversify the teaching profession.…”
Section: Challenges Having a Racially Diverse Facultymentioning
confidence: 99%
See 1 more Smart Citation
“…Black males in particular, may struggle with the thought of becoming teachers given their often highly negative interactions with schools and schooling as K-12 students including low expectations, racial stereotypes, microagressions, and disproportionate discipline and punishment (Goings & Bianco, 2016;Walker, Goings, & Wilkerson, 2019;Woodson & Bristol, 2020). Moreover, low pay, the "de-professionalization" of teaching, a lack of acceptance of Black males outside of secondary, mainstream education, and discriminatory hiring practices further complicate their recruitment into K-12 classrooms (see Bristol & Goings, 2019;D'Amico, Pawlewicz, Earley, & McGeehan, 2017;White, Woodward, Graham, Milner, & Howard, 2019).…”
Section: Black Males and The Choice (Not) To Teachmentioning
confidence: 99%
“…These trends offer a structural trap for prospective Black teachers in that more accessible access to licensing through alternative certification is contingent on less expensive, less rigorous preparation, accelerating the influx of unqualified and inexperienced teachers into communities of color (White et al, 2020). Carter et al revealed in a 2017 study that over half of the newly hired Black teachers were certified through an alternate route, compared to just 22% of other first-year teachers.…”
Section: Alternative Certification Programsmentioning
confidence: 99%